TIPE-TIPE POLA ASUH DALAM PENDIDIKAN KELUARGA - Rekno Handayani; Imaniar Purbasari; Deka Setiawan (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2020)
This study aims to analyze the type of parenting in the family education of SD 1 Gulang students, Mejobo District, Kudus Regency.This research is a qualitative descriptive study conducted in Gulang Village, Mejobo District, Kudus Regency. The research subjects were grade 4 students of SD 1 Gulang. The data collection techniques used include direct observation, interviews, research documentation, and note taking. Interviews were conducted with parents of students who implemented parenting, students, and teachers who were the main informants. In analyzing the data, the Milles Huberman model was used, namely the analysis was carried out including data collection, data reduction, data presentation and conclusion drawing.The results showed that SD 1 Gulang students received family education from parents who applied various types of parenting styles. The following shows several types of parenting that are found (1) democratic patterns, democratic parenting is a form of parenting that is cooperative for children, but there are certain limitations, this pattern is able to provide maximum education in the family so that children have good character and social attitudes. (2) neglect, this form of parenting has a tendency for parents not to be involved at all in the child's life, (3) authoritarian, the family provides strict supervision to the child so that the parents are quite dominant in the child's life and (4) permissive, the parents In providing assistance, only providing needs without providing good family education to children. Of the four types of parenting found, it is known that democratic patterns are parenting styles that have a positive role for children. The three other parenting styles do not have a positive role. As a result, students become passive and cannot socialize well, so that family education is important for a child's life, especially SD 1 Gulang.